2010
DOI: 10.2147/ndt.s12433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quetiapine on sleep architecture in patients with unipolar or bipolar depression

Abstract: Objective:To determine the effect of adjunctive quetiapine therapy on the sleep architecture of patients with bipolar or unipolar depression. Methods: This is a prospective, single-blind, repeated measures polysomnographic study. Sleep architecture was analyzed by overnight polysomnography, and subjective sleep quality was measured using the Pittsburgh Sleep Quality Index. The Hamilton Rating Scale for Depression, Montgomery Asberg Depression Rating Scale, Young Mania Rating Scale, and Clinical Global Impressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Antidepressants rarely improve sleep continuity; most improvements are seen with tricyclic antidepressants. Increased total sleep time and sleep efficiency, as well as decreased sleep latency and total wake time were observed here, similar to that seen with other augmentation agents such as risperidone [ 64 ], but different than quetiapine, which does not alter sleep continuity in depression [ 65 ]. The beneficial effects of olanzapine treatment on sleep continuity may be due to its diverse pharmacological profile.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Antidepressants rarely improve sleep continuity; most improvements are seen with tricyclic antidepressants. Increased total sleep time and sleep efficiency, as well as decreased sleep latency and total wake time were observed here, similar to that seen with other augmentation agents such as risperidone [ 64 ], but different than quetiapine, which does not alter sleep continuity in depression [ 65 ]. The beneficial effects of olanzapine treatment on sleep continuity may be due to its diverse pharmacological profile.…”
Section: Discussionsupporting
confidence: 83%
“…Although previous studies of augmentation to SSRIs have shown R suppression, the degree of polypharmacy was less in these studies, as each participant was only taking one antidepressant [ 70 ]. This may reflect the changes often seen with psychotropic treatment to sleep architecture [ 65 , 71 ]. Few medications have been reliably shown to suppress R sleep and also increase sleep continuity and SWS.…”
Section: Discussionmentioning
confidence: 99%
“…Another non-RCT noted there was no significant change in respiratory disturbance index between baseline and quetiapine. Unfortunately, however, neither data nor statistical inference were provided (Gedge et al, 2010). an individual has OSA continues to evolve with early definitions defining OSA as ≥5 respiratory events/h of sleep (Kapur et al, 2017).…”
Section: Current Understanding Of the Effects Of Quetiapine On Sleep-...mentioning
confidence: 99%
“… 12 A previous study suggests that an adjunctive quetiapine treatment can alter the sleep architecture in patients with MDD or bipolar depression. 13 In addition, it also has an active metabolite, norquetiapine ( N -desalkyl quetiapine), which has a high affinity for norepinephrine transporters and partially agonizes to serotonin 5-HT 1A receptors. 14 Hence, the efficacy of quetiapine in ameliorating depressive symptoms in adults with unipolar and bipolar depression may be associated with antagonizing at 5-HT 2A , α 2b adrenergic, and D 2 receptors and agonizing at a 5-HT 1A receptor and its effect on sleep architecture.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Hence, the efficacy of quetiapine in ameliorating depressive symptoms in adults with unipolar and bipolar depression may be associated with antagonizing at 5-HT 2A , α 2b adrenergic, and D 2 receptors and agonizing at a 5-HT 1A receptor and its effect on sleep architecture. 13 , 15…”
Section: Introductionmentioning
confidence: 99%